2013
DOI: 10.1051/0004-6361/201220429
|View full text |Cite
|
Sign up to set email alerts
|

Self-calibration: an efficient method to control systematic effects in bolometric interferometry

Abstract: Context. The QUBIC collaboration is building a bolometric interferometer dedicated to the detection of B-mode polarization fluctuations in the cosmic microwave background. Aims. We introduce a self-calibration procedure related to those used in radio-interferometry to control a wide range of instrumental systematic errors in polarization-sensitive instruments.Methods. This procedure takes advantage of the need for measurements on redundant baselines to match each other exactly in the absence of systematic effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 17 publications
0
50
0
5
Order By: Relevance
“…Unlike other ground-based experiments, all the QUBIC mirrors are inside the cryostat (4 K) and after the polariser in the optical chain, reducing the effect of any instrumental polarisation due to them. An autocalibration technique, making use of redundant baselines, has been developed 6,7 so that QUBIC will achieve unprecedented control of systematics along with a sensitivity comparable to that of more traditional imaging polarimeters. Simulations have shown that this first module could constrain the tensor-to-scalar ratio down to ( ) = 0.01 after a two-year survey 4 .…”
Section: Qubic and The Cosmic Microwave Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other ground-based experiments, all the QUBIC mirrors are inside the cryostat (4 K) and after the polariser in the optical chain, reducing the effect of any instrumental polarisation due to them. An autocalibration technique, making use of redundant baselines, has been developed 6,7 so that QUBIC will achieve unprecedented control of systematics along with a sensitivity comparable to that of more traditional imaging polarimeters. Simulations have shown that this first module could constrain the tensor-to-scalar ratio down to ( ) = 0.01 after a two-year survey 4 .…”
Section: Qubic and The Cosmic Microwave Backgroundmentioning
confidence: 99%
“…Waveguide switches placed between the horns in each back-to-back pair will allow signals from individual horns or baselines to be turned on and off. The switches will be opened and closed regularly while QUBIC observes a calibration source to allow self-calibration of the system 6,7 . QUBIC will be used as a synthetic imager, observing the fringes from all baselines simultaneously.…”
Section: The Beam Combinermentioning
confidence: 99%
See 1 more Smart Citation
“…Even with 1 s per baseline (corresponding to a full day dedicated to self-calibration) we can reduce significantly the E → B leakage. This leakage can be further reduced by spending more time in self-calibration (adapted from [3]). The parameter r represents the ratio between the amplitudes of the tensor and scalar fluctuations during inflation.…”
Section: Measurement and Self-calibrationmentioning
confidence: 99%
“…1, left panel): thanks to this feature, a given baseline can be characterised independently, and a set of baselines realising the same Fourier mode (equivalent baselines) can be used to obtain a largely redundant number of measurements of an artificial far-field source to recover the systematics of the instrument, encoded in a certain number of unknown parameters describing horn cross-polarisation, transmission unbalancing, etc. (see [6] for a comprehensive discussion). In this way, the instrument can be self-calibrated, and a novel way of handling systematics can be exploited.…”
Section: Qubic As An Adding Interferometermentioning
confidence: 99%